VITAMIN D DEFICIENCY - E. A. Potrokhova; N. V. Sobotyuk; S. V. Bochantsev; S. A. Golochalova; E. E. Shlykova; N. G. Mazhukina (Union of pediatricians of Russia, 2014)
Spread of vitamin D deficiency in children of various ages has not been studied in the Russian Federation. Numerous studies of foreign authors indicate high importance of this issue in many regions of the world, including southern territories with high level of insolation. The review analyzes issues of optimal calcidol level and vitamin D deficiency effect on the immune system. The authors support the hypothesis that vitamin D deficiency results in derangement of congenital and adaptive immunity and may be considered one of the etiological factors of frequent respiratory morbidity in children.